A nesting area suitability model (MISN) to estimate the population parameters of Rock Partridge, Alectoris graeca orlandoi, in Rieti and Frosinone Provinces - Andrea Amici; Fioravante Serrani; Settimio Adriani; Bruno Ronchi; Marco Bonanni; Riccardo Primi (Rivista Italiana di Ornitologia - Research in Ornithology, 2012)
In the last decades the Rock Partridge has undergone a decline throughout the entire area of distribution. The abundance of Apennine Rock Partridge, Alectoris graeca orlandoi, in the provinces of Frosinone and Rieti has been estimated with the pre-reproductive census technique of playback in the areas suitable for nesting. The methodology for assessing the suitability of the site for nesting of Apennine Rock Partridge was based on a parametric procedure that included the attribution of score to biotic (land use) and abiotic (elevation, slope, etc.) factors producing Andrea Amici 1, Fioravante Serrani 1, Settimio Adriani 2, Bruno Ronchi 1, Marco Bonanni 3 & Riccardo Primi 1 USO DEL MODELLO DI IDONEITÀ DI SITO PER LA NIDIFICAZIONE (MISN) PER LA STIMA DEI PARAMETRI DI POPOLAZIONE DELLA COTURNICE APPENNINICA, ALECTORIS GRAECA ORLANDOI, NELLE PROVINCE DI RIETI E DI FROSINONE, AGGIORNATA AL DICEMBRE 2009 Amici, Serrani, Adriani, Ronchi, Bonanni & Primi different layers. The layers obtained were interpolated to obtain a nesting site suitability model for Rock Partridge (MISN). In the province of Rieti the playback census was conducted in the years 2005-2006-2007 obtaining stable population data: 42-45 nesting pairs, and a density of 0.50 to 0.60 and 0.12 to 0.14 pairs/100 ha of land suitable for nesting, in areas where there is a hunting ban and where hunting is permitted respectively. In the province of Frosinone in 2007 were estimated 76 breeding pairs and a density of 0.6 and 0.28 pairs/100 ha in areas of ban hunting and free hunting respectively.